Standardised classification of the aetiology of bronchiectasis using an objective algorithm. Issue 6 (14th December 2017) - Araújo, David; Shteinberg, Michal; Aliberti, Stefano; Goeminne, Pieter C.; Hill, Adam T.; Fardon, Tom; Obradovic, Dusanka; Dimakou, Katerina; Polverino, Eva; De Soyza, Anthony; McDonnell, Melissa J.; Chalmers, James D.
Bronchiectasis (BE) is a chronic and progressive respiratory disease with multiple possible causes [1, 2]. Many require a specific therapy and thus, a systematic aetiologic evaluation is recommended by guidelines [3]. Studies have shown wide heterogeneity in the proportion of different aetiologies identified among centres [4–8], which can be partially justified because of geographical risks factors, but may also reflect variations in testing practice or in the definitions of aetiology used [9]. The proportion of patients classified as idiopathic varies (26–74%) across the literature, and this variability is likely to be somewhat linked to a lack of use of a standard aetiological algorithm [4–8]. The use of a standardised aetiological algorithm in bronchiectasis can improve the diagnosis of underlying cause http://ow.ly/5dga30gxrq3